Connectivity Editing for Quad-Dominant Meshes - Peng, Chi-Han; Wonka, Peter (Computer graphics forum, 2013)
We propose a connectivity editing framework for quad‐dominant meshes. In our framework, the user can edit the mesh connectivity to control the location, type, and number of irregular vertices (with more or fewer than four neighbors) and irregular faces (non‐quads). We provide a theoretical analysis of the problem, discuss what edits are possible and impossible, and describe how to implement an editing framework that realizes all possible editing operations. In the results, we show example edits and illustrate the advantages and disadvantages of different strategies for quad‐dominant mesh design.